IMPLEMENTASI KEGIATAN MERONCE DALAM MENINGKATKAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK TASKA BANDAR LAMPUNG - Ranala , Najjati (UNISAN JURNAL, 2025)
This study aims to describe the implementation of stringing activities in improving the fine motor skills of children aged 4-5 years at TK Taska Bandar Lampung. Fine motor skills are very important skills for early childhood, because they influence children’s independence and readiness to participate in further learning activities. One effective method to develop children’s fine motor skills is through stringing activities, namely arranging small objects such as beads or straws into strings in certain patterns. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects consisted of class teachers, students, and the principal. The results of the study indicate that stringing activities are carried out routinely in daily thematic learning, with a play-while-learning approach. The teacher provided directions, engaging media, and concrete examples of stringing to help children understand the activity’s objectives. Children demonstrated improved fine motor skills, such as the ability to grasp small objects, control hand and finger movements, and eye-hand coordination. Factors contributing to the success of this activity included the availability of varied media, active teacher involvement, and children’s enthusiasm for participating. Inhibiting factors included children’s lack of concentration and limited time. Thus, stringing activities have proven effective in stimulating fine motor development in children aged 4-5 years.